2019
DOI: 10.3311/ppee.13431
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Different Bio-based Polymers for Wiring Boards

Abstract: The paper gives a review of experiments for the application of biodegradable, sustainable polymers as a wiring board material. In the paper two different biobased materials and the standard PCB materials FR4 and FR2 were compared. The investigations refer to mechanical, electrical performance, surface quality the flammability and applicability for Polymer Thick Film Technology (PTFT) of the biobased material. The biobased materials are polylactic acid (PLA) mixed with different contents of cellulose acetate (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It is concluded that most of the presented PCB substrate materials can be used in explicit reflow profile modelling later, with negligible error caused by the uneven temperature along the thickness of the board; however PLA shows more considerable temperature differences (<20 per cent compared to the full temperature scale) pointing to larger model imprecision. Finally, the use of PLA substrates results in more significant temperature differences along the bulk thickness of the applied board, which further complicates the use of such thermally sensitive materials (Henning et al , 2019) in assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that most of the presented PCB substrate materials can be used in explicit reflow profile modelling later, with negligible error caused by the uneven temperature along the thickness of the board; however PLA shows more considerable temperature differences (<20 per cent compared to the full temperature scale) pointing to larger model imprecision. Finally, the use of PLA substrates results in more significant temperature differences along the bulk thickness of the applied board, which further complicates the use of such thermally sensitive materials (Henning et al , 2019) in assembly.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper the following PCB types and materials were investigated: FR4 (epoxy with glass fibre reinforcement, handled as a composite in our calculations), Polyimide [commonly used for flexible boards (Fjelstad, 2011)], BeO and Al 2 O 3 [used in technical ceramic-based circuits in microwave and power electronics applications (Licari and Enlow, 1998)] and biodegradables, such as PLA (polylactic-acid) and CA (cellulose acetate) [under intensive research for use in electronics (Schramm et al , 2012; Henning et al , 2019; Zhang et al , 2019)]. Table I.…”
Section: Methodsmentioning
confidence: 99%
“…According to the type of the fitted function it can be categorized as a linear and non-linear optimization task. The literature contains a lot of different methods to solve this problem with the required accuracy [15][16][17][18][19][20][21][22][23][24][25][26]. Most of these measurements use the gradient-based solvers, the Gauss-Newton Algorithm or the Levenberg-Marquardt Algorithm, which use the fact that these problems can be expressed by the rules of the Quadratic Programming (QP) [27,28].…”
Section: Nonlinear Curve Fitting With āRtapmentioning
confidence: 99%
“…The proposed method and setup is especially useful for special applications, such as pin in paste technology [14], or soldering on special, heat sensitive materials, such as biodegradables [15,16], which is a special current and future application of the presented solution.…”
Section: Introductionmentioning
confidence: 99%